A Sequential Algebraic Parametric Identification Approach for Nonlinear Vibrating Mechanical Systems. Issue 4 (21st February 2017) - Beltran‐Carbajal, F.; Silva‐Navarro, G.; Trujillo‐Franco, L. G.
Abstract: A systematic on‐line algebraic parametric identification method in time domain is proposed for active vibration control on nonlinear vibrating mechanical systems. The identification is performed iteratively, to reduce the computational effort of the parameter estimation process, for finite or infinite dimensional large flexible structures into an interest bandwidth. Position signals are only required to algebraically and quickly estimate the parameters of multiple degrees‐of‐freedom nonlinear vibrating mechanical systems. Then, an adaptive‐like output feedback tracking dynamic control scheme is introduced to assess the efficiency and effectiveness of the closed‐loop parameter estimation algorithms. Some simulation results are included to provide evidence of the efficient dynamic performance of the proposed parametric identification approach combined with asymptotic trajectory tracking control.